Moving Open Repositories out of the Blind Spot of Initiatives to Correct the Scholarly Record - Bordignon, Frédérique (Learned Publishing, 2025)
ABSTRACT Open repositories were created to enhance access and visibility of scholarly publications, driven by open science ideals emphasising transparency and accessibility. However, they lack mechanisms to update the status of corrected or retracted publications, posing a threat to the integrity of the scholarly record. To explore the scope of the problem, a manually verified corpus was examined: we extracted all the entries in the Crossref × Retraction Watch database for which the publication date of the corrected or retracted document ranged from 2013 to 2023. This corresponded to 24,430 entries with a DOI, which we use to query Unpaywall and identify their possible indexing in HAL, an open repository (second largest institutional repository worldwide). In most cases (91%), HAL does not mention corrections. While the study needs broader scope, it highlights the necessity of improving the role of open repositories in correction processes with better curation practices. We discuss how harvesting operations and the interoperability of platforms can maintain the integrity of the entire scholarly record. Not only will the open repositories avoid damaging its reliability through ambiguous reporting, but on the contrary, they will also strengthen it.